C-Kit plays a critical role in induction of intravenous tolerance in experimental autoimmune encephalomyelitis - Safavi, Farinaz (Immunol Res, 2015)
c-Kit (CD117) is a tyrosine kinase receptor found in various types of immune cells. It has been shown that c-Kit plays a role in the pathogenesis of multiple sclerosis, an inflammatory demyelinating disorder of the CNS. Recent data have suggested an immunoregulatory effect of c-Kit. We therefore examined the role of c-Kit in autoantigen-induced i.v. tolerance in experimental autoimmune encephalomyelitis (EAE), an animal model of MS. Our results show that induction of intravenous tolerance against EAE in B6 mice is characterized by increased numbers of CD117+ cells and altered mast-cell associated molecules in the periphery and in the CNS. W(−sh) (c-Kit deficient) mice were resistant to i.v autoantigen-induced tolerance, with increased proinflammatory cytokine production in the periphery. I.v. autoantigen in WT mice suppressed production of proinflammatory cytokines IFN-γ and IL-6 and up-regulated expression of FoxP3, a transcription factor of Tregs; however, in W(−sh) mice IFN-γ and IL-6 were increased with a failure of FoxP3 induction upon i.v. autoantigen injection, and is thus a mechanism for resistance to i.v. tolerance induction in these mice. We conclude that c-kit signaling has a regulatory role in i.v. tolerance and could be a target for potential immunotherapy in autoimmune disorders.